Point mutagenesis in mouse reveals contrasting pathogenetic effects between MEN2B‐ and Hirschsprung disease‐associated missense mutations of the RET gene. (28th April 2020) - Nakatani, Taichi; Iwasaki, Mitsuhiro; Yamamichi, Atsuhiro; Yoshioka, Yuta; Uesaka, Toshihiro; Bitoh, Yuko; Maeda, Kosaku; Fukumoto, Takumi; Takemoto, Tatsuya; Enomoto, Hideki
Abstract: Missense mutations of the RET gene have been identified in both multiple endocrine neoplasia (MEN) type 2A/B and Hirschsprung disease (HSCR: congenital absence of the enteric nervous system, ENS). Current consensus holds that MEN2A/B and HSCR are caused by activating and inactivating RET mutations, respectively. However, the biological significance of RET missense mutations in vivo has not been fully elucidated. In the present study, we introduced one MEN2B‐associated (M918T) and two HSCR‐associated (N394K and Y791F) RET missense mutations into the corresponding regions of the mouse Ret gene by genome editing ( Ret M919T, Ret N396K and Ret Y792F ) and performed histological examinations of Ret ‐expressing tissues to understand the pathogenetic impact of each mutant in vivo. Ret M919T/+ mice displayed MEN2B‐related phenotypes, including C‐cell hyperplasia and abnormal enlargement of the primary sympathetic ganglia. Similar sympathetic phenotype was observed in Ret M919T/‐ mice, demonstrating a strong pathogenetic effect of the Ret M918T by a single‐allele expression. In contrast, no abnormality was found in the ENS of mice harboring the Ret N394K or Y791F mutation. Most surprisingly, single‐allele expression of RET N394K or Y791F was sufficient for normal ENS development, indicating that these RET mutants exert largely physiological function in vivo. This study reveals contrasting pathogenetic effects between MEN2B‐ and HSCR‐associated RET missense mutations, and suggests that some of HSCR‐associated RET missense mutations are by themselves neither inactivating nor pathogenetic and require involvement of other gene mutations for disease expressivity. Abstract : Biological significance of RET missense mutations has largely been unclear. In this study, MEN2B‐ and Hirschsprung disease‐associated RET missense mutations were introduced into the mouse Ret locus by CRISPR/Cas9‐mediated genome editing. Although strong pathogenetic effects were observed in mice carrying the MEN2B‐associated mutation, no pathogenicity was observed in mice harboring HSCR‐associated mutations.